Medierapportering om demokratihot - En kvalitativ analys av svensk nyhetsmedias rapportering om Chat Control 2.0 - Sjunnesson Ståhl,Nils (2025)
In may of 2022 a EU law was proposed with the intent of stopping the online spread of CSAM (Child Sexual Abuse Material) by monitoring all online communication in search of child exploitation material. Since then, the proposed law has come under scrutiny due to the suggested surveillance of civilians without any need for criminal suspicion. Today the proposed law is most commonly known as Chat Control 2.0 and is still active for EU voting despite the heavy criticism. The purpose of this study is to analyse Swedish news media coverage surrounding the proposed CSAM law with the intention of identifying discourse significant as to how the law is portrayed through journalism. The study is based on the theoretical framework of social constructivism where the world is interpreted as being constructed through discourse. Thus, phrasing in news coverage can significantly influence public perception. Through a discourse analysis three of Sweden's most influential news media outlets and their publishings regarding the subject during 2022-2023 were analysed. The study concludes that Swedish news media coverage simultaneously portrays Chat Control 2.0 both as a positive course of action in order to protect children as well as a threat to democratic principles.
Keywords: Chat Control 2.0; CSAM; CSAR; Förordning; Barnskydd; Övervakning; Demokrati; Rättigheter; Diskurs; Media; Socialkonstruktivism; Teknopopulism; Diskursanalys